2013
DOI: 10.1093/brain/awt201
|View full text |Cite
|
Sign up to set email alerts
|

The exact science of stroke thrombolysis and the quiet art of patient selection

Abstract: The science of metric-based patient stratification for intravenous thrombolysis, revolutionized by the landmark National Institute of Neurological Disorders and Stroke trial, has transformed acute ischaemic stroke therapy. Recanalization of an occluded artery produces tissue reperfusion that unequivocally improves outcome and function in patients with acute ischaemic stroke. Recanalization can be achieved mainly through intravenous thrombolysis, but other methods such as intra-arterial thrombolysis or mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 252 publications
3
47
0
1
Order By: Relevance
“…Stroke, which mainly causes ischemic events, is the third cause of death worldwide and the main cause of chronic, severe adult disability. The current therapy can restore cerebral blood flow within a narrow time window to prevent damage to the Bpenumbra^area, which surrounds the infarct core [40]. In order to increase the therapeutic time window, neuroprotection is an alternative or adjunct approach to thrombolysis, targeting the cerebral parenchyma in the acute ischemic phase [41].…”
Section: Discussionmentioning
confidence: 99%
“…Stroke, which mainly causes ischemic events, is the third cause of death worldwide and the main cause of chronic, severe adult disability. The current therapy can restore cerebral blood flow within a narrow time window to prevent damage to the Bpenumbra^area, which surrounds the infarct core [40]. In order to increase the therapeutic time window, neuroprotection is an alternative or adjunct approach to thrombolysis, targeting the cerebral parenchyma in the acute ischemic phase [41].…”
Section: Discussionmentioning
confidence: 99%
“…1 Although IV t-PA may be effective, several factors, including the location, size, and characteristics of the thrombus, may lead to tPA resistance in about 50% of patients. 2 We already know that the chances of recanalisation with IV t-PA are even more limited in cases of proximal large artery occlusions. In a landmark study 3 it was shown that the overall chances of recanalisation with IV thrombolysis are around 30%, but less when the thrombi are in the middle cerebral artery stem (24%) or in the proximal internal carotid artery (8%).…”
Section: Discussionmentioning
confidence: 99%
“…16 Thrombolytic treatment may result in adverse effects, such as systemic bleeding, angioedema 17 and symptomatic intracranial haemorrhage (sICH), which is the most disabling and potentially fatal complication, occurring in approximately 3-4% of patients. 12 By definition, sICH usually results in worse disability than would have occurred without thrombolytic treatment and in a small proportion of patients can be responsible for death.…”
Section: Structure Of the Reportmentioning
confidence: 99%
“…14, 17 Given the recorded variation in thrombolysis treatment rates, 19 the lack of expert consensus on several exclusion criteria for treatment (such as recent medical procedures and spontaneous improvement rate) 20 and the ongoing debates regarding the efficacy of thrombolysis, [21][22][23][24][25][26] it is important to understand factors which influence clinicians' decisions about whether or not to give intravenous thrombolysis to patients with acute ischaemic strokes, using a method that reflects decision-making in practice. 27,28 Trial evidence and guidelines on intravenous thrombolysis…”
Section: Structure Of the Reportmentioning
confidence: 99%
See 1 more Smart Citation